Design of a low-voltage constant transconductance rail-to-rail CMOS operational amplifier - Gao Yuhong; Li Junlong (Dianzi Jishu Yingyong, 2020)
This paper presents a rail-to-rail constant transconductance operational amplifier input stage. The proposed circuit changes the tail current of the input differential pairs dynamically for a constant-gm by using dummy input differential pairs. The problem which causes total gm variation is input pairs and dummy input pairs can not take effect at the same time with the common-mode input voltage changes, because the tail current transistor of the input pairs are in triode region when the input pairs are turned off, the dummy input pairs will enter subthreshold region from cut-off region before the input pairs when common-mode voltage changes. The effect of this problem is more obviously in low supply voltage design. To solve this problem, compensate current sources is added to the tail current transistors of each dummy input differential pairs for lower gm variation. The gm of this Op Amp′s input stage varies around ±2%.